Size dependence of defect-induced room temperature ferromagnetism in undoped ZnO nanoparticles - Xu, Xiaoyong (2013)
We report the intrinsic room-temperature ferromagnetism in undoped ZnO nanoparticles with different sizes synthesized by a wet chemical method at different temperatures. Electron paramagnetic resonance, X-ray photoelectron spectroscopy, and photoluminescence measurements demonstrate clearly the singly charged oxygen vacancies are the main defects, and the relative occupancy of that decreases with increasing sizes and annealing temperatures. Importantly, a direct correlation between the ferromagnetism and the relative concentration of the singly charged oxygen vacancies is established, which suggests that the singly charged oxygen vacancies play a crucial role in modulating ferromagnetic behaviors. Moreover, the size-dependent ferromagnetism can be manipulated conveniently by changing of the surface–volume ratio, which is in favor of future electronic and spintronic application.